«ШАРИЯР» ДӘСТАНЫНДА МИЙНЕТ ТӘРБИЯСЫ МӘСЕЛЕЛЕРИ - Алламбергенов, Е.К. (FAN va JAMIYAT, 2020)
The article deals with thorough analysis of the problems on upbringing for labour, which is considered to be one of the main types of the educational-upbringing process on the example of creating a fruit garden by Shariyar, the main character of the Karakalpak folk epos “Shariyar”. Thus there is confirmed folk notions, educational-upbringing views on the fact that human is perfect by his labour, not only by ordinary labour, but by labour which is fullfilled for the sake of wellfare of the people. On the example of an industriousity of the image of Shariyar it is made a conclusion, that the perfectness of a human labour is closely connected with his aim, dreams and positive properties of his spiritual moral qualities.